2022
DOI: 10.1002/clt2.12144
|View full text |Cite
|
Sign up to set email alerts
|

Artificial intelligence processing electronic health records to identify commonalities and comorbidities cluster at Immuno Center Humanitas

Abstract: Background Comorbidities are common in chronic inflammatory conditions, requiring multidisciplinary treatment approach. Understanding the link between a single disease and its comorbidities is important for appropriate treatment and management. We evaluate the ability of an NLP‐based process for knowledge discovery to detect information about pathologies, patients' phenotype, doctors' prescriptions and commonalities in electronic medical records, by extracting information from free narrative text … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 46 publications
0
4
0
1
Order By: Relevance
“…NLP systems have the potential to improve epidemiology disease awareness; NLP has been utilized in previous studies to extract information from unstructured clinical notes, including the dermatology setting 16–18,24 . Morandini et al 16 used NLP to assess clinical notes to identify diseases that present together as comorbidities.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…NLP systems have the potential to improve epidemiology disease awareness; NLP has been utilized in previous studies to extract information from unstructured clinical notes, including the dermatology setting 16–18,24 . Morandini et al 16 used NLP to assess clinical notes to identify diseases that present together as comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…NLP systems have the potential to improve epidemiology disease awareness; NLP has been utilized in previous studies to extract information from unstructured clinical notes, including the dermatology setting. [16][17][18]24 Morandini et al 16 used NLP to assess clinical notes to identify diseases that present together as comorbidities. Through NLP, they reported that, of 2057 patient records, the most common conditions that occur together were oral allergy syndrome and urticaria, angioedema and urticaria, and rhinitis and asthma.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nell'esperienza clinica reallife sono comuni le situazioni complesse, con pazienti con una storia di patologia di lunga durata, sottoposti a trattamenti diversi anche per le comorbilità presenti, per i quali la decisione terapeutica risulta complicata e non chiaramente definita dalle Linee Guida. Per questi pazienti l'intervento multidisciplinare è determinante; l'introduzione di approcci innovativi come l'utilizzo dell'intelligenza artificiale può rappresentare un supporto nell'identificazione di migliori strategie terapeutiche, in relazione all'elevato numero di possibili comorbilità (20).…”
Section: La Multidisciplinarietà Come Strumento Per Il Miglioramento ...unclassified